Modelling the dynamic flight behaviour of birds in different frames of reference - Kempton, JA (2022)
In this thesis I consider two aspects – energetics and guidance – of two dynamic flight behaviours performed by birds – dynamic soaring and prey pursuit. Uniting the thesis is the collection and modelling of bird trajectory data in different frames of reference to make inferences on dynamic flight behaviour. In particular, I collect data in a camera-fixed reference frame to model the dynamic soaring flight trajectories of Manx shearwater in an aerodynamic reference frame, whereas I model the attack trajectories of Harris’ hawks in both an inertial and a background frame of reference using data collected in an Earth-fixed frame of reference. The output of my investigation into the energetics of dynamic soaring is the first empirical demonstration of dynamic soaring outside the albatrosses, the formulation of a new metric for identifying and quantifying dynamic soaring, and the demonstration that the large-scale distribution of the Manx shearwater is affected by their dynamic soaring behaviour. The output of my investigation into the guidance of prey pursuit is the finding that Harris’ hawk attack trajectories are well modelled by the proportional navigation (PN) guidance law commonly used by homing missiles. However, I also show that a guidance law that can be mechanised using only visual information – rather than the inertial and visual information required by PN – also successfully fits attack trajectory data. Finally, I propose a method for analysing eye-in-head movements during dynamic flight in birds, and I find that Harris’ hawks limit eye-in-head movement during terminal pursuit, a necessary condition to implement PN guidance. In being reflective about the reference frames in which I model bird behaviour and, in cases, by modelling the same data in different reference frames, I expose the utility of the reference frame concept in analysing biological systems.